Perancangan Spud Pada Dredger Barge 25 Meter - Novrialdo Maratua; Hendra Saputra; Lalu Giat Juangsa Putra (Jurnal Teknologi dan Riset Terapan (JATRA), 2020)
Operation of ships with special functions such as dredgers or commonly called Dredger Barge requires special support such as spuds. In addition to being able to replace anchors more effectively, it can also facilitate supporting vessels such as Anchor Handling Tug and ensure safety while operating. In this study planning and analysis needs to be done in order to estimate the reaction and the condition of the spud and the spud holder at the time of operation. The study approach uses Solidwork software to simulate the strength test of the material as well as the safety of the spud and the spud holder when receiving sea wave pressure, ocean currents and wind in extreme weather using Mild Steel (ASTM (S) A36) material. The results of the simulation of the strength and feasibility test of the spud and the spud holder were obtained with a von mises spud value of 0.0856 N / mm2 and a von mises value on the spud holder of 15.5 N/mm2 with the parameter value of the von mises spud and spud holder of 188 N / mm2. Furthermore, the simulation results of the shear stress value on the spud are 2.37x10-7 N/mm2 and the shear stress value on the spud holder is 3.32x10-5 N/mm2 with the parameter value of the spear shear stress and the spud holder of 141 N/mm2. Furthermore, the simulation results of the Deflection value for the spud is 0.00116 mm and the deflection value for the spud holder is 0.117 mm with the deflection spud parameter value of 80 mm, and the deflection parameter for the spud holder is 10 mm. The spud and spud holders in this design are feasible in production and have been guaranteed safety and feasibility by referring to the parameters according to the standards of the Bureau Veritas and American Institute of Steel Construction rules